The Efficacy of Implementing Cognitive Behavioral Therapy for Sleep Disorder - Abdul Rahim,; Mohammed Fayaz S,; N Sai Supra Siddhu, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Sleep disorders (SDs) in young adulthood are a growing public health concern due to their impact on well-being, productivity, and social interactions. These disorders are linked to severe health risks, including hypertension, diabetes, and cardiovascular diseases, emphasizing the need for adequate sleep. Objectives: To review the prevalence, etiology, and non-pharmacological treatment of sleep disorders in young adults, with a focus on the efficacy of Cognitive Behavioral Therapy for Insomnia (CBT-I). Methods: A review of the literature was conducted to examine the prevalence and contributing factors of SDs in young adults. Evidence-based approaches to treatment, particularly CBT-I, were evaluated, along with barriers to its implementation and strategies for improving accessibility. Results: CBT-I is an evidence-based intervention targeting insomnia by addressing maladaptive thoughts and behaviors. It improves sleep quality, duration, and mental health through key components like sleep education, cognitive therapy, sleep hygiene, and relaxation techniques. Implementation of CBT-I includes various formats such as individual and group therapy, workshops, mobile apps, online programs, and telehealth. Studies highlight its efficacy: email-delivered CBT-I improves sleep metrics, group-based interventions reduce maladaptive beliefs, and app-based CBT-I enhances sleep quality and alleviates insomnia symptoms. Telehealth and workshops demonstrate comparable effectiveness to in-person therapy, while individualized CBT-I significantly outperforms sleep hygiene practices. Digital CBT-I expands accessibility, but adherence and privacy concerns remain barriers. Conclusions: Prioritizing sleep health and adopting evidence-based treatments like CBT-I can mitigate the effects of sleep disorders in young adults. Addressing barriers through awareness campaigns, training programs, and digital CBT-I delivery could enhance its implementation, improving quality of life and promoting a healthier society.